V. Lenin and Cultural Heritage - Repšys, Jonas (Problemos, 1969)
On the basis of Lenin’s theoretical heritage and dialectical-materialistic analysis of culture as a social phenomenon the author attempts to disclose the interrelation between socialism and the culture of the past. Guided by the Leninist principles of continuity in the development of culture the author points out theoretical groundlessness and practical adventurism of the “proletcult” approach to creating the culture of the socialist society. Criticism of bourgeois conceptions on the socialist culture is given.